Prevention and therapy of preterm birth: guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF registry number 015/025, September 2022) : part 2 with recommendations on the tertiary prevention of preterm birth and on the management of preterm premature rupture of membranes = Prävention und Therapie der Frühgeburt : Leitlinie der DGGG, OEGGG and SGGG (S2k-Level, AWMF-Registernummer 015/025, September 2022) : Teil 2 mit Empfehlungen zur tertiären Prävention der Frühgeburt und zum Management des frühen vorzeitigen Blasensprungs - Berger, Richard; Abele, Harald; Bahlmann, Franz; Doubek, Klaus; Felderhoff-Müser, Ursula; Fluhr, Herbert; Garnier, Yves; Grylka-Baeschlin, Susanne; Hayward, Aurelia; Helmer, Hanns; Herting, Egbert; Hoopmann, Markus; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Aim: The revision of this guideline was coordinated by the German Society for Gynecology and Obstetrics (DGGG), the Austrian Society for Gynecology and Obstetrics (OEGGG) and the Swiss Society for Gynecology and Obstetrics (SGGG). The aim of the guideline is to improve the prediction, prevention and management of preterm birth based on evidence from the current literature, the experience of members of the guidelines commission, and the viewpoint of self-help organizations. Methods: The members of the contributing professional societies and organizations developed recommendations and statements based on international literature. The recommendations and statements were presented and adopted using a formal process (structured consensus conferences with neutral moderation, written Delphi vote). Recommendations: Part 2 of this short version of the guideline presents statements and recommendations on the tertiary prevention of preterm birth and the management of preterm premature rupture of membranes.
Gesehen am 27.08.2024